AKT controls NLRP3 inflammasome activation by inducing DDX3X phosphorylation. Issue 19 (7th September 2021) - Guo, Xingchen; Chen, Sheng; Yu, Weiwei; Chi, Zhexu; Wang, Zhen; Xu, Ting; Zhang, Jian; Jiang, Danlu; Guo, Yuxian; Fang, Hui; Zhang, Kailian; Li, Mobai; et al.
Abstract : The NLRP3 inflammasome, a critical component of the innate immune system, induces caspase‐1 activation and interleukin‐1β maturation and drives cell fate toward pyroptosis. However, the mechanism of NLRP3 inflammasome activation still remains elusive. Here we provide evidence that AKT regulates NLRP3 inflammasome activation. Upon NLRP3 activation, AKT activity is inhibited by second stimulus‐induced reactive oxygen species. In contrast, AKT activation leads to NLRP3 inhibition and improved mitochondrial fitness. Mechanistically, AKT induces the phosphorylation of the DDX3X (DEAD‐box helicase 3, X‐linked), a recently identified NLRP3 inflammasome component, and impairs the interaction between DDX3X and NLRP3. Furthermore, an AKT agonist reduces NLRP3‐dependent inflammation in two in vivo models of LPS‐induced sepsis and Alum‐induced peritonitis. Altogether, our study highlights an important role of AKT in controlling NLRP3 inflammasome activation. Abstract :